TRANSISI KHALIFAH UMAYYAH: DARI MUAWIYAH BIN ABU SUFYAN KE YAZID BIN MUAWIYAH (661-683 M) - agus mahfudin setiawan (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2019)
Transition is a period of change, a turning point of social change both in the form of structure (socio-political) and culture (socio-cultural). Power on the basis of the faith shown by the Prophet Muhammad had a very fundamental influence, for Muslim government in the year 661-683 M.  The transition of power shifted from the electoral system senior companions to hereditary. This transition period was based on feelings of dissatisfaction with the latest leadership of Ali Bin Abi Talib. The aftermath of this is the war between the supporters of rule (Ali bin Abi Thalib). This conflict is based on seniority and the authority of the apostle's friendship with the opposing government, the descendants of the Hashim and Umayyah. Islamic politics of  indeed inseparable from the interaction between one government and another, a transition of power and politics that is so dynamic in accordance with the demands of the context of the era at that time. This paper aims to illustrate that the Umayyah government system was not standard at all, but moved dynamically.